(untitled) (Urdimento: Revista de Estudos em Artes Cênicas, 2022)
Performativity, based on the materiality of the scene, intends to pierce the face of the so-called “theatrical” and promulgates an escape from the sign, from the semantics, from fiction; but in this search, wouldn’t you restore theatricality and representation in other possibilities? In the search for the oscillation and unmasking of representation as a semblance, wouldn’t the performative as materiality of the scene generate another representation, another semblance in sensation and perception, but always a representation of an unrepresentable infinite in its entirety? This communication seeks to problematize these questions from the affirmation of the impossibility of the absence of representation in the materiality of the performance and for that, it problematizes the concept of materiality and the real in the contemporary scene.